Differences in carbon and nitrogen metabolism of soft japonica rice in southern China during grain filling stage under different light and nitrogen fertilizer conditions and their relationship with rice eating quality - Ma, Zhongtao; Cao, Jiale; Chen, Xi; Yu, Jianghui; Guodong, Liu; Xu, Fangfu; Hu, Qun; Li, Guangyan; Zhu, Ying; Zhang, Hongcheng; Wei, Haiyan (Frontiers in Plant Science, 2025)
Light and nitrogen are crucial environmental factors that significantly impact rice growth and quality formation. Currently, there is a lack of systematic research on how light and nitrogen affect carbon and nitrogen metabolism during grain filling, subsequently affecting the eating quality of rice. To address this gap, field experiments were conducted under varying light intensities and nitrogen fertilizer levels to investigate the changes in carbon and nitrogen metabolism during grain filling, the eating quality of rice at maturity, and the relationship between them. The findings revealed that, 50% light intensity suppressed carbon metabolism while stimulating nitrogen metabolism, resulting in a reduction in the C/N ratio, decreased starch content by 4.30% to 5.59%, and elevated protein content by 21.31% to 29.70%, thereby leading to decreased rice eating quality by 10.06% to 11.42%. Conversely, the application of panicle fertilizer boosted nitrogen metabolism while hindering carbon metabolism, leading to a decrease in the C/N ratio, increased protein content by 21.31% to 29.70%, and reduced starch content by1.60% to 2.93%, thereby leading to decreased rice eating quality by 4.13% to 6.71%. Correlation analysis revealed a significant positive correlation between the C/N ratio and carbon metabolism-related enzyme activities and products, along with a significant negative correlation with nitrogen metabolism-related enzyme activities and products, suggesting that the C/N ratio can serve as an indicator of carbon and nitrogen metabolism levels. Further analysis revealed a significant positive relationship between the C/N ratio and taste value, indicating that higher levels of carbon metabolism promote the development of good rice eating quality, while nitrogen metabolism exerts an opposing influence. In summary, notable variances in carbon and nitrogen metabolism were observed within the same japonica rice cultivar under diverse light and nitrogen fertilizer conditions. These metabolic differences impact the synthesis of starch and protein in the endosperm, ultimately influencing rice quality. Our study contributes to a more profound comprehension of the regulation of carbon and nitrogen metabolism in rice by light and nitrogen fertilizer, as well as their role in determining eating quality.